2011
DOI: 10.1007/s00421-011-2175-x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of exercise-induced hypoxemia on blood redox status in well-trained rowers

Abstract: Exercise-induced arterial hypoxemia (EIAH), characterized by decline in arterial oxyhemoglobin saturation (SaO(2)), is a common phenomenon in endurance athletes. Acute intensive exercise is associated with the generation of reactive species that may result in redox status disturbances and oxidation of cell macromolecules. The purpose of the present study was to investigate whether EIAH augments oxidative stress as determined in blood plasma and erythrocytes in well-trained male rowers after a 2,000-m rowing er… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 59 publications
(81 reference statements)
0
27
1
Order By: Relevance
“…Indeed, some of the largest reported changes in redox homeostasis occurred in the general preparation phases of periodised training programs, such as when athletes are returning to training after a transition period of minimal training and detraining (Kyparos et al 2009;Kyparos et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, some of the largest reported changes in redox homeostasis occurred in the general preparation phases of periodised training programs, such as when athletes are returning to training after a transition period of minimal training and detraining (Kyparos et al 2009;Kyparos et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The exercise protocols used to assess ARH were sport-specific and ranged from 2,000 m simulated rowing races, maximal treadmill and cycling tests, multiple Wingate tests, and an interval swim test. Only two studies reported the analytical variability of the assays used [25,107], and only the cycling study of Cuevas et al [109], and the two rowing studies of Kyparos et al [25,107] controlled for changes in plasma volume (PV). Biomarkers of lipid peroxidation either increased or did not change pre-to post-exercise challenge, with large increases (45-100 %) for thiobarbituric acid reactive substances (TBARS) pre-to post-simulated 2,000 m rowing races [24,25,107], a modest increase (16 %) in swimmers pre-to post-interval swimming (8 9 100 m) [110], and no change reported in one cycling study utilising multiple Wingate tests [109].…”
Section: Evidence For Alterations In Redox Homeostasis (Arh) Followinmentioning
confidence: 98%
“…Only two studies reported the analytical variability of the assays used [25,107], and only the cycling study of Cuevas et al [109], and the two rowing studies of Kyparos et al [25,107] controlled for changes in plasma volume (PV). Biomarkers of lipid peroxidation either increased or did not change pre-to post-exercise challenge, with large increases (45-100 %) for thiobarbituric acid reactive substances (TBARS) pre-to post-simulated 2,000 m rowing races [24,25,107], a modest increase (16 %) in swimmers pre-to post-interval swimming (8 9 100 m) [110], and no change reported in one cycling study utilising multiple Wingate tests [109]. Two other assays were used to assess lipid peroxidation, conjugated dienes (CD) and RBC malondialdehyde (MDA) as follows: Pittaluga et al [108] reported a small increase pre-to post-maximal exercise in professional road cyclists for CD, and in distance runners, Dane et al [111] reported no change for RBC MDA pre-to post-maximal exercise.…”
Section: Evidence For Alterations In Redox Homeostasis (Arh) Followinmentioning
confidence: 98%
See 2 more Smart Citations